2016
DOI: 10.1007/s00408-016-9883-2
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Indices in Patients with Coal Workers’ Pneumoconiosis

Abstract: Platelet indices may be considered as disease markers for pneumoconiosis in coal miners and as a useful indicator of the progression of pneumoconiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Previous studies have indicated an association between PCT and various cardiovascular events, such as a worse outcome in acute coronary syndrome 33,34 and presence of cardiac syndrome X, 35 and various pulmonary diseases such as pulmonary tuberculosis 25,26 and coal workers' pneumoconiosis. 36 Makhlouf et al 5 showed that PCT is higher in diabetic or nondiabetic patients with COPD compared with healthy controls, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have indicated an association between PCT and various cardiovascular events, such as a worse outcome in acute coronary syndrome 33,34 and presence of cardiac syndrome X, 35 and various pulmonary diseases such as pulmonary tuberculosis 25,26 and coal workers' pneumoconiosis. 36 Makhlouf et al 5 showed that PCT is higher in diabetic or nondiabetic patients with COPD compared with healthy controls, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…8 However, the hemoglobin levels have no significant differences in patients with different stages. 23 In our study, there were no significant differences in hemoglobin and hematocrit between I/II stage pneumoconiosis and III stage pneumoconiosis. We consider that these discrepant results may be attributed to different occupational exposure factors and time in patients with pneumoconiosis.…”
Section: Discussioncontrasting
confidence: 55%
“…These biomarkers include IL6, IL8, TNFα, CC16, Npnt and serum HO-1 [20][21][22][23]. However, although these biomarkers are useful in understanding the pathogenesis and progression of silicosis, it is not possible to identify a biomarker with the greatest potential for silica-related diseases with complex pathogenesis [20,24,25].…”
Section: Discussionmentioning
confidence: 99%